Strategi Manajemen Lanskap yang Dikembangkan untuk Taman Kota di Kota Purwokerto - Annisaa Farah Fitriana; Regan Leonardus Kaswanto; Nurhayati Hadi Susilo Arifin (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2023)
The Green Open Space (RTH) development program for 2021-2025 states that Dinas Lingkungan Hidup (DLH) of Banyumas Regency manages city parks in Purwokerto City. Despite the fact that developments and optimisations took place in both 2021 and 2022, landscape conditions still need attention. So, this study aims to evaluate the management of urban parks’ landscapes and to analyse perceptions of community members who visited the city parks across Purwokerto City regarding city park management. Study findings will be used to develop a sustainable landscape management strategy. This research implements a mixed method in data collection, a Chi-Square test, and a SWOT-based analysis. Results show landscape management works well when intensive maintenance is enforced despite labour shortages. Visitors’ perception is central in assessing the management of a city park, especially when analysis is done based on the most significant Chi-Square test results. Male respondents of Taman Satria Berkoh and male-female respondents to Purwokerto Square have a strong perception of the role of temperature comfort and performance of park managers in landscape management. Respondents aged between 26-34 years in Taman Mas Apung Kemambang, as well as respondents with status as residents of Purwokerto City and Banyumas Regency in Ahmad Yani Literacy Park, focused their perceptions on the importance of facilities provision in landscape management. Ultimately, this research proposes a landscape management strategy of "hold and maintain."Keywords: city park; landscape manajement; Purwokerto city; visitor perseptionAbstrakDinas Lingkungan Hidup (DLH) Kabupaten Banyumas mengelola taman kota di Kota Purwokerto dalam program pengembangan Ruang Terbuka Hijau (RTH) 2021-2025. Meskipun ada pengembangan dan optimalisasi di tahun 2021-2022, kondisi lanskap masih perlu diperhatikan. Sehingga penelitian ini bertujuan mengevaluasi manajemen lanskap taman kota dan menganalisis persepsi pengunjung taman kota di Kota Purwokerto. Hasilnya akan digunakan untuk menyusun strategi manajemen lanskap yang berkelanjutan. Metode penelitian menggunakan analisis mix method, uji Chi-Square, dan analisis SWOT. Hasil menunjukkan bahwa manajemen lanskap taman berjalan baik menggunakan pemeliharaan intensif, meskipun ada kekurangan tenaga kerja. Persepsi pengunjung menjadi sorotan utama penilaian taman, terutama berdasarkan hasil uji Chi-Square yang paling signifikan. Dari jenis kelamin, responden laki-laki di Taman Satria Berkoh dan responden laki-laki maupun perempuan di Alun-Alun Purwokerto, mempunyai persepsi yang kuat terhadap kenyamanan suhu, dan kinerja pengelola taman dalam pengelolaan lanskap. Responden yang berusia antara 26-34 tahun di Taman Mas Apung Kemambang, serta responden dengan status sebagai warga Kota Purwokerto dan Kabupaten Banyumas di Taman Literasi Ahmad Yani, memfokuskan persepsinya akan pentingnya penyediaan fasilitas dalam pengelolaan lanskap. Hasil strategi manajemen lanskap yang dikembangkan dan diusulkan adalah "hold and maintain”.Kata kunci: taman kota; manajemen lanskap; Kota Purwokerto; persepsi pengunjung